Soft Islamophobia - Islam, Namira (Religions, 2018)
This article explores Islamophobia as a system of oppression by examining policies and practices found in liberal or left-leaning anti-Islamophobia spaces in the United States that limit the efficacy of the fight for justice. These include the reification of Muslim as a cultural category of brown foreigners, the lack of structural analysis around anti-Muslim hate, and the discomfort with and erasure of Islam as a faith in favor of cultural Muslims. The article then briefly proposes alternate ways forward that center the Muslims most affected by the intersections of race, class, gender, and religion in work against Islamophobia so that advocates can more effectively and directly address a system of Islamophobia.